Effect of humic acid (potassium humate) on growth and yield of turmeric (Curcuma longa L.) in an alfisol - Sankaran, K Baskar, K (Journal of Spices and Aromatic Crops, 2005)
A field experiment was conducted at Mattuvarayapuram (Coimbatore District, Tamil Nadu) to evaluate the effect of lignite humic acid (HA) on growth and yield of turmeric (Curcuma longa) in an alfisol. The study revealed that application of 100% NPK 050:60:108 kg ha") with HA applied to soil 10 kg ha’)’" foliar spray (HA 0.1%) + rhizome dipping (HA 0.1%) significantly enhanced the growth and yield attributes, fresh and cured rhizome yield of turmeric.